DC / AC pure sine wave power inverter / Mohd Azam Abd Hamid - Abd Hamid, Mohd Azam (2010)
This project focuses on DC to AC power inverters, which aim to efficiently transform a DC power source to a high voltage AC source, similar to power that would be available at an electrical wall outlet. Inverters are used for many applications, as in situations where low voltage DC sources such as batteries, solar panels or fuel cells must be converted so that devices can run off of AC power. To simulate the circuit of the project MATLAB/SIMULINK was used to know the properties of the waveform, output voltage, Total Harmonic Distortion (THD) of the inverter and etc. The microcontroller was used to generate the Pulse Width Modulation (PWM) techniques for full bridge inverter application. It's utilized for storing pre-programmed duty cycles with its memory by using mikro Basic PRO for PIC. This eliminated the need for large analog components which often have a tendency to become unstable.